The murderous Middle Ages. - Marshall, Michael (New Scientist, 2024)
Alice Roberts's book "Crypt" explores the history of Britain's Middle Ages through the study of bones. Each chapter focuses on a specific grave and tells a unique story, covering topics such as the St Brice's Day Massacre, the killing of Archbishop Thomas Becket, the sinking of the Mary Rose, and the practice of walling oneself off in a church. Roberts draws on a variety of sources, including bones, historical documents, and ethnography, to provide a comprehensive understanding of the time period. The book delves into dark subjects such as epidemics, mass murder, and suffering, reminding readers that history is not always comforting but offers valuable lessons.